Interrogating quality: minority language, education and imageries of competence in Nepal - Pradhan, U (Routledge, 2019)
Quality education is increasingly considered essential for human development. However, the mainstream approach to quality as a neutral technology often ignores deeply embedded issues of power relations. This article interrogates the taken-for-granted idea of ‘quality education’ by exploring the ways in which students navigate the assumption of quality education in two mother-tongue schools in Nepal. Drawing on the concept of language ideology, this article shows that the perceived social prestige associated with a language choice is closely intertwined with the discourse of quality education in Nepal. In this context, the students secure ‘imageries of competence’ by repeatedly drawing attention to more acceptable indicators of ‘quality’ such as high examination scores, English proficiency and continuation of higher studies. This article foregrounds the power relations embedded in the perception of quality education and intends to be of wider analytical relevance to other socially heterogeneous contexts beyond Nepal.